DISEMINASI TEKNIS PELAKSANAAN UU NO. 6 TAHUN 2014 TENTANG DESA BAGI APARATUR PEMERINTAHAN DESA MUNDING KECAMATAN BERGAS KABUPATEN SEMARANG - Arif Hidayat (Journal of Dedicators Community, 2017)
Village governance based on Law No. 6 of 2014 concerning the Village (Village Act) is needed by the village officials Munding Bergas District of Semarang Regency. This dissemination using interactive discussion techniques to strengthen their understanding of the technical implementation of the Law on the Village contained in various regulation Villages of Rural Development Year 2015. Lessons to be learned from this activity is that the consistency of rural development must be supported by the commitment, awareness and active participation all interested parties on the progress of the village, as a forum for the public welfare . Keyword: Village Act, Village Government, Participation